H/ACA Small RNA Dysfunctions in Disease Reveal Key Roles for Noncoding RNA Modifications in Hematopoietic Stem Cell Differentiation - Cristian Bellodi; Mary McMahon; Adrian Contreras; Dayle Juliano; Noam Kopmar; Tomoka Nakamura; David Maltby; Alma Burlingame; Sharon A. Savage; Akiko Shimamura; Davide Ruggero (Cell Reports, 2013)
Noncoding RNAs control critical cellular processes, although their contribution to disease remains largely unexplored. Dyskerin associates with hundreds of H/ACA small RNAs to generate a multitude of functionally distinct ribonucleoproteins (RNPs). The DKC1 gene, encoding dyskerin, is mutated in the multisystem disorder X-linked dyskeratosis congenita (X-DC). A central question is whether DKC1 mutations affect the stability of H/ACA RNPs, including those modifying ribosomal RNA (rRNA). We carried out comprehensive profiling of dyskerin-associated H/ACA RNPs, revealing remarkable heterogeneity in the expression and function of subsets of H/ACA small RNAs in X-DC patient cells. Using a mass spectrometry approach, we uncovered single-nucleotide perturbations in dyskerin-guided rRNA modifications, providing functional readouts of small RNA dysfunction in X-DC. In addition, we identified that, strikingly, the catalytic activity of dyskerin is required for accurate hematopoietic stem cell differentiation. Altogether, these findings reveal that small noncoding RNA dysfunctions may contribute to the pleiotropic manifestation of human disease.